To find the distance between the points E \((-6, 1)\) and F \((2, -5)\) using the distance formula, we use the following formula:
\[ d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \]
Where \((x_1, y_1)\) are the coordinates of point E and \((x_2, y_2)\) are the coordinates of point F. Substituting in the specific coordinates:
- \(x_1 = -6\), \(y_1 = 1\)
- \(x_2 = 2\), \(y_2 = -5\)
The distance formula setup would be:
\[ d = \sqrt{(2 - (-6))^2 + (-5 - 1)^2} \]
This simplifies to:
\[ d = \sqrt{(2 + 6)^2 + (-5 - 1)^2} \] \[ d = \sqrt{(8)^2 + (-6)^2} \]
None of the provided responses are exactly correct because they contain errors in the setup. However, the closest response, employing the correct adjustments, would be:
d = square root of open paren 2 minus negative 6 close paren squared plus open paren negative 5 minus 1 close paren squared end root
Since the intended expression and calculations involve:
- \(x_2 - x_1 = 2 - (-6) = 2 + 6 = 8\)
- \(y_2 - y_1 = -5 - 1 = -6\)
To sum it all up, the official option setup was not available, but the closely matching answer with positioning correction should be indicated.